Implementation of Advanced Sound and Visual Technology to Increase Architectural Space Quality for in Proposed Autism Explorative Edupark Centre in Kuala Lumpur - Fadzli, Farah Ashiqeen; Kadir, Tengku Anis Qarihah Raja Abdul (MAJ - Malaysia Architectural Journal, 2022)
In the modern era, visual technology offers significant impacts, especially in the architecture industry and sound technology. It is known that this modern civilisation is ocular-centric and relies heavily on visions. However, a thorough understanding of the aesthetic of visuals and immersive sound technology, especially towards the community with different abilities (this study focus on the autism community), may enhance the spatial planning is poorly known. Visuals and sound have influenced each other and brought us the most surprising outcomes. Sound and visual has advanced as a digital information method and have immersed into all life features, including giving impacts on visual perception in terms of architectural spatial design quality. Advance sound and visual technology – the extended reality technology has been implemented in a variety of fields these recent years, including medical, industrial design, modelling and production, entertainment, and leisure activities, interior and exterior design, virtual friends, the internet of things, as well as spatial design enhancer. This research aims to study the impacts of integrating state-of-the-art sound and visual technology in enhancing architectural space quality to elevate the engagement between architectural space and users with autism spectrum disorder (ASD). This research is based on data obtained from a survey questionnaire that polled autistic child’s perceptions and acceptance regarding integrating state-of-the-art sound and visual technology in architectural spaces.